Revolutionary Perspectives for Leadership Preparation: A Case of a Networked Improvement Community. (March 2022) - Thornton, Margaret E.; Barakat, Maysaa; Grooms, Ain A.; Locke, Leslie Ann; Reyes-Guerra, Daniel
This qualitative study describes and interprets how two educational leadership programs, participants in the UCEA (University Council for Educational Administration) Program Design Network Improvement Community, identified and responded to a problem of practice by focusing on the needs of each program regarding the recruitment, selection, admission, and retention of candidates from underrepresented groups. Through collaborative learning and research, the programs were able to guide the change processes of their institutional structures to focus on attracting more diverse applicant pools that are more focused on issues of diversity in the schools they will serve.